Covid-19 containment measures adopted in bone marrow transplantation service - Rodrigues,Jéssica Alline Pereira (2020)
ABSTRACT Objective: To describe the experience of nursing, in adopting containment measures, in the care of patients undergoing hematopoietic stem cell transplantation to avoid COVID-19. Methods: Experience report. Results: Containment measures involve those recommended by major health organizations, such as hand hygiene, social isolation, identification and monitoring of suspected or confirmed cases; and also the local measures implemented in the health service, such as the reduction in the number of hospitalizations for transplantation, clinical screening of outpatients entering the service, monitoring of respiratory signs and symptoms, the allocation of specific isolation rooms for those suspected of the disease and testing of symptomatic patients. Final considerations: The nurse is responsible for the challenge of planning nursing care to prevent the spread of coronavirus in a high-risk population and to implement measures based on available evidence, periodically updated.